ANALISIS KEUNTUNGAN PEDAGANG SAYUR KELILING PADA MASA PANDEMI COVID 19 DI PERUMAHAN CHT DESA SEA SATU KECAMATAN PINELENG KABUPATEN MINAHASA (Profit Analysis of Vegetable Traders in the Covid 19 Pandemic Time CHT Residence in Sea Village, Pineleng District, Minahasa Regency) - Yudha Pranata Mangowal; Leonardus R. Rengkung; Rine Kaunang (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2021)
This study was to analyze the profits of the mobile vegetable traders in the CHT Residence in Sea Satu Village, Pineleng District, Minahasa Regency. The research was conducted for three months, from November 2019 to January 2020. The data used were primary data and secondary data. The results showed that the average profit earned by the mobile vegetable traders was IDR 506,564 / month.Keywords: Profit Analysis, Vegetable Trader